Unveiling Photo-Thermal-Electrical Performance in Robust, Self-Healing, and Anti-Freezing Cellulose-MXene Eutectogels for Advanced Hemostasis - Jiang, Chuang; Ning, Hengli; Liu, Wei; Li, Zhikun; Zhu, Huiwu; Li, Long; Hou, Qingxi; Chen, Chaoji; Cheng, Bowen (Nano-Micro Letters, 2026)
Uncontrolled hemorrhage, resulting from trauma or surgery, presents a critical challenge in medical care. This study introduces a novel eutectogel, a multifunctional material synthesized using choline chloride/phytic acid derived deep eutectic solvents (CP-DES)-mediated cellulose-MXene polyacrylamide, aimed at addressing hemostatic needs. The eutectogel combines photothermal and thermoelectric effects to accelerate hemorrhage control, significantly reducing blood loss and hemostasis time. Unlike existing hemostatic materials, our design leverages the synergistic effects of photothermal heating and thermoelectric current, enhancing coagulation and promoting tissue repair. The innovation lies in the integration of DES to stabilize MXene, optimizing its photothermal and thermoelectric properties, and enabling rapid gelation, self-healing, and anti-freezing capabilities. In vitro and in vivo tests demonstrate the material’s superior performance in hemostasis compared to traditional gauze, highlighting its potential for trauma care and surgical applications. This approach sets a new paradigm in the development of advanced, multifunctional biomedical materials for hemostasis and beyond. Highlights: 1 A deep eutectic solvent-mediated strategy integrates cellulose and MXene into a polyacrylamide network, enabling rapid gelation, and long-term MXene stabilization (>690 days). 2 The eutectogel exhibits tissue-adhesive, self-healing, anti-freezing properties, high ionic conductivity, and efficient photothermal conversion, enabling multimodal sensing and synergistic photothermoelectric hemostasis. 3 First demonstration of synergistic photothermoelectric hemostasis, where localized photothermal heating and Seebeck-driven microcurrents synergistically accelerate coagulation, achieving superior hemostatic performance with significantly reduced blood loss and hemostasis time.